Ruthenium Complexes of Rigid, Dianionic, Tetradentate N‐Donor Ligands and their Potential as Catalysts for Water Oxidation. Issue 3 (5th December 2022) - Rajabi, Sheida; Rüttger, Franziska; Lücken, Jana; Dechert, Sebastian; John, Michael; Meyer, Franc
Abstract: Two mononuclear ruthenium(II) complexes based on dianionic N4 ligands and with axial pyridines have been prepared and characterized crystallographically (1 ) or by 2D NMR spectroscopy using residual dipolar couplings (2 ). The N4 ligands provide a constrained equatorial coordination with one large N−Ru−N angle, and additional non‐coordinating N atoms in case of 2 . Their redox properties have been investigated (spectro)electrochemically, and their potential to serve as water oxidation catalysts has been probed using cerium ammonium nitrate (CAN) at pH 1.0. Complex 1 undergoes rapid degradation, likely via ligand oxidation, whereas 2 is more rugged and exhibits 80 % efficiency in the Ce IV ‐driven water oxidation, with a high initial turnover frequency (TOFi ) of 3.07×10 −2 s −1 (at 100 equiv. CAN). The initial rate of O2 evolution exhibits 1 st order dependence on catalyst concentration, suggesting a water nucleophilic attack mechanism. Repeated addition of CAN and control experiments show that high ionic strength conditions (both NO3 − and Ce III ) significantly decrease the TOF. Abstract : Two Ru II complexes with equatorial N4 ligands that enforce one wide N−Ru−N angle show very different performance in Ce IV driven water oxidation. 1 undergoes oxidative degradation, whereas 2 featuring non‐coordinating N atoms is more rugged and exhibits good efficiency and high initial turnover frequency. The non‐symmetric structure of 2 has been established by 2D NMR spectroscopy using residual dipolar couplings.